Molecular Bases and Phenotypic Determinants of Aromatase Excess Syndrome - Maki Fukami; Makio Shozu; Tsutomu Ogata (International Journal of Endocrinology)
Aromatase excess syndrome (AEXS) is a rare autosomal dominant disorder characterized by gynecomastia. This condition is caused by overexpression of CYP19A1 encoding aromatase, and three types of cryptic genomic rearrangement around CYP19A1, that is, duplications, deletions, and inversions, have been identified in AEXS. Duplications appear to have caused CYP19A1 overexpression because of an increased number of physiological promoters, whereas deletions and inversions would have induced wide CYP19A1 expression due to the formation of chimeric genes consisting of a noncoding exon(s) of a neighboring gene and CYP19A1 coding exons. Genotype-phenotype analysis implies that phenotypic severity of AEXS is primarily determined by the expression pattern of CYP19A1 and the chimeric genes and by the structural property of the fused exons with a promoter function (i.e., the presence or the absence of a natural translation start codon). These results provide novel information about molecular mechanisms of human genetic disorders and biological function of estrogens.